A Lateral Flow Immunochromatographic Assay (LFIA) Strip Reader Based on Scheduler and 8051 IP Core. (1st October 2016) - Gao, Yue Ming; Vai, Mang I; Mak, P.; Hang, Pun Sio; Wei, Jian Chong; Wang, Zhi-Jiong
Abstract : This paper reports a fuzzy differential equations approach for the modeling of initial condition uncertainty for a proportional derivative closed-loop control of a direct current motor. Uncertainties are considered on the precision of the sensing devices installed on a driver. The closed-loop system is designed for a plant modeled with fuzzy differential equations. Satisfactory analytic and numerical results for the position regulation problem for ideal case and also considering perturbed initial conditions are reported.